The Influence of TikTok on the Political Perspectives of Civics Students of the Class of 2025, State University of Malang - Annifatimah Safira; Devi Putri Azalina; Novita Handayani; Waffi Maulana Fatahillah; Salsabi Cahyani Limas Wari; Surya Desismansyah (Pancasila and Civics Education Journal (PCEJ), 2026)
ABSTRACTTikTok is currently the most influential social media platform in shaping public political opinion, including that of students. This study aims to analyze the impact of TikTok on the political views of students enrolled in the 2025 Pancasila and Citizenship Education undergraduate program at Malang State University and to identify the obstacles students face when expressing their political opinions on TikTok. This study uses a quantitative method with a random survey model using random sampling techniques. Data collection was conducted through Google Forms. This study produced 1) A clear picture of the extent to which TikTok social media influences the political awareness of PPKn students. 2) The obstacles encountered, particularly by TikTok users and PPKn students.Keywords: SocialMedia, TikTok, Political Opinions, PPKn Students ABSTRAKTikTok di era ini merupakan media sosial paling massif dalam membentuk opini politik masyarakat tak terkecuali opini politik mahasiswa. Penelitian ini bertujuan untuk menganalisis dampak penggunaan media sosial TikTok terhadap cara pandang politik mahasiswa Program Studi S1 Pendidikan Pancasila dan Kewarganegaraan Angkatan 2025 Universitas Negeri Malang dan apa saja kendala yang ditemukan saat mahasiswa menyatakan opini politiknya melalui TikTok. Penelitian ini menggunakan metode kuantitatif dengan model survey secara acak menggunakan teknik random sampling. Adapun pengumpulan datanya melalui Google Form. Penelitian ini menghasilkan 1) Gambaran yang jelas mengenai sejauh mana pengaruh media sosial TikTok dalam membentuk kesadaran politik mahasiswa PPKn. 2) kendala yang ditemukan khususnya pengguna TikTok dan mahasiswa PPKn.Kata Kunci: Media Sosial, TikTok, Opini Politik, Mahasiswa PPKn